Pollination by Three Species of Stingless Bees (Hymenoptera: Meliponini) Increase Seed Set of Mustard (Brassica rapa L.: Brassicaceae) - Asmini Asmini; Tri Atmowidi; Sih Kahono (Bogor Agricultural University, Indonesia, 2022)
Pollination and fertilization are critical factors in horticultural cultivation to increase seed production. In this study, we measured the visiting activity and pollination of three species of stingless bees, i.e., Tetragonula laeviceps, Lepidotrigona terminata, and Heterotrigona itama in mustard (Brassica rapa). Visiting activity of stingless bees were observed in mustard plants caged by an insect screen. The observations were done visually per hour, starting from 07:00 until 16:00, using the focal sampling method. The visiting activities observed were flower handling time, foraging rate, and total visit per plant. We also measured the pollen load of each stingless bee species. Results showed the highest foraging rate occurred in H. itama (28.38 flowers/5 minutes), followed by T. laeviceps (27.88 flowers/5 minutes), and L. terminata (27.85 flowers/5 minutes), respectively. The longest flower handling time was found in H. itama (40.15 seconds), followed by T. laeviceps (35.25 seconds), and H. terminata (34.84 seconds). Whereas, the highest total visiting time occurred in H. itama (40.10 minutes), followed by T. laeviceps (37.47 minutes), and L. terminata (36.76 minutes). Heterotrigona itama has a highest pollen load (36,650 pollen grains), followed by L. terminata (26,940 pollen grains), and T. laeviceps (9,700 pollen grains), respectively. Pollination by the stingless bees increase 27-40% the number of pods per plant, 32-72% the number of seeds per pod, 32-54% of seed weight per pod, and 18-36% of seed germination of mustard.